Varying humidity increases emission of volatile nitrogen-containing compounds from building materials. (November 2021) - Hall, Emma C.; Haines, Sarah R.; Marciniak, Katarzyna; Goldstein, Allen H.; Adams, Rachel I.; Dannemiller, Karen C.; Misztal, Pawel K.
Abstract: Volatile organic compounds (VOCs) are released from building materials in the indoor, environment at different rates dependent upon relative humidity (RH) level. However, RH indoors commonly fluctuates, and the effects of fluctuating RH on VOC emissions, is unknown. The goal of this study was to characterize VOC emissions from carpet and, drywall under static and dynamic RH conditions using proton-transfer-reaction time of, flight mass spectrometer (PTR-TOF-MS). For both carpet and drywall, the cycling of, RH between two different RH levels resulted in differences in the amounts and, compositions of the emission profiles compared to static RH conditions. For example, the total sum of emissions (ΣVOCs) was 88% elevated in dynamic RH (12 h. 85%, 12, hr. 50%) conditions compared to static RH conditions (24 h. 85%) for carpets, with, nitrogen-containing emissions increasing from 0.0065 mg.hr-1.m-2 to 3.02 mg.hr-1.m-2. Emissions of some chemical identities, like C4H9ONH+ (putative morpholine), appeared to be "activated" by cycling RH with emissions going from 0 mg.hr-1.m-2 at, static RH to 15 mg.hr-1.m-2 and 150 mg.hr-1.m-2 at dynamic RH for carpet and, drywall, respectively. The addition of house dust decreased the ΣVOCs from building, materials by 32–85%, except when RH conditions were sufficiently elevated to support, microbial growth. Many of the compounds observed in this study may be related to, material degradation processes. Overall, fluctuating RH changes the VOC emissions, profile from building materials at static RH by increasing emissions and emitting more, nitrogen-containing compounds, which could have important implications for human, chemical exposures. Highlights: Dynamic relative humidity increased the total VOC emissions from building materials. VOC increase was driven by "activation" of a specific group of compounds. A joint emission mechanism is likely for specific compounds. Majority of the specific compounds include nitrogen. Dust on the surface of materials dampened emissions at most RH conditions.